Transitivity in uniform approach theory - Y. J. Lee; B. Windels (International Journal of Mathematics and Mathematical Sciences)
We introduce a notion of transitivity for approach uniformities and approach uniform convergence spaces, yielding reflective subconstructs of AUnif and AUCS. Further, we investigate how these new categories are related to uACHY, uACHY U , and uMET, and we show that these relationships are similar to those in the classical case.